CHARACTERIZATION OF IMMUNE PHENOTYPES AS PREDICTIVE BIOMARKERS FOR RESPONSE TO THE α4β7 INTEGRIN BLOCKER, VEDOLIZUMAB. (21st January 2021) - Martinez, Catherine; Cusguen, Maria Alejandra Quintero; Pignac-Kobinger, Judith; Crynen, Gogce; Fernandez, Irina; Santander, Ana; Delmas, Amber; Kerman, David; Damas, Oriana; Deshpande, Amar; Burgueno, Juan; Abreu, Maria; et al.
Abstract: The etiology of inflammatory bowel disease (IBD) is unknown. However, chronic inflammation from T cell activation and its subsequent tissue damage is implicated in the pathogenesis of IBD. Vedolizumab (VDZ), a monoclonal antibody against α4β7 integrin that prevents T cell homing to intestinal mucosae, has shown efficacy in treating both ulcerative colitis (UC) and Crohn's disease (CD), with greater efficacy in UC. We aimed at identifying immunophenotypic and gene regulatory characteristics that could predict which IBD patients will benefit from VDZ therapy. Peripheral blood mononuclear cells and lamina propria mononuclear cells (PBMC and LPMC) were isolated before treatment with VDZ and after treatment (PBMC; between weeks 14 and 22). PBMCs/LPMCs were stained for T cell markers, gut homing receptors, and other immune cell markers. Sorted CD4 + memory (Tmem) and regulatory (Treg) T cells underwent RNA sequencing (RNA-seq). Clinical response was defined as at least a two-point drop in partial Mayo scores (UC) and Harvey-Bradshaw (CD) indices following VDZ therapy. Using an agnostic approach to the flow cytometry data, we examined cell clustering by CytofKit and related immunophenotypic markers to disease type and responsiveness. We performed differential gene analysis (DEseq2) of RNA-seq data on T cell populations from the periphery and lamina propria. In total, 71 patients were enrolled and 37 received VDZ. Of 37 patients, 14 responded (37.8%); 21% of UC patients, 16% of CD patients. A cohort of patients responsive with long term VDZ therapy, despite initial refractoriness, was identified. Unsupervised clustering revealed the largest immunophenotypic differences between ileal and colonic biopsies, regardless of IBD subtype or inflammation state. Likewise, T cells, both Tmems and Tregs, showed the greatest number of DEGs between tissue types. In patients who received VDZ, we examined immunophenotypic biomarkers able to predict response. Specific clusters found to predict response were either specific to disease state or independent of disease state. Tissue-related immunophenotypes isolated by flow and RNA signatures in T cell subsets, especially Tregs, offered the best predictors of response, compared to blood. We examined changes in PBMC and T cell gene expression after VDZ in blood. After VDZ treatment, especially in UC, we saw an increase in α4β7+ T cells that were also positive for the gut specific CCR9 marker. In the peripheral blood following VDZ treatment, we saw a decrease in inflammatory pathway activation in Tregs. The results show that intestinal profiling better represents CD and UC than peripheral blood. Using a combination of clinical data, immunophenotyping, and gene expression allows for a more comprehensive view of the mucosal immune response in IBD. These biomarkers may allow rational use of VDZ given its safety profile.